Patients with hydrocephalus presenting in the psychiatric clinic: report of two cases Pacientes com hidrocéfalo e predominância de distúrbios psíquicos: relato de dois casos - Wolfgang W. May (Arquivos de Neuro-Psiquiatria)
Two patients with major mental symptomatology and few neurological signs were presented who on further studies were revealed to have unsuspected hydrocephalus. This was due to an obstructive lesion at the level of the aqueduct present since birth or for many years. Both presented with a rather unusual clinical picture so that they were first considered to suffer from a psychiatric illness. Radiographic contrast studies established the diagnosis in both cases and led to successful treatment in one of them. The first patient made an uneventful recovery after a shunting operation. The other had no such operation and died of an unrelated disease some time later. A constellation of declining mental functions with or without behavioral disturbance and few or minor neurologic signs and an abnormal electroencephalogram should include in the differential diagnosis "occult" hydrocephalus which is a potentially correctable condition. The psychiatrist might be the first one to see this type of patient and to initiate the appropriate evaluation. Em dois pacientes com sintomatologia mental predominante e poucos sinais neurológicos, exames complementares mostraram tratar-se de hidrocéfalo por lesão obstrutiva ao nível do aqueduto de Sylvius, existente desde o nascimento ou por muitos anos. Ambos foram internados por apresentar um quadro clínico não usual que a princípio levou a pensar em doença psiquiátrica. Exames radiológicos contrastados estabeleceram o diagnóstico em ambos os casos e permitiram o tratamento eficaz de um deles. O primeiro paciente teve grande melhora após intervenção cirúrgica na qual foi feita derivação ventrículo-atrial. O outro paciente não pôde ser operado e faleceu de afecção intercorrente. Discutindo os casos, o autor procura chamar a atenção para a importância da avaliação diagnóstica das demências orgânicas visando ao despistamento de uma condição potencialmente corrigível.